PENGARUH PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASI (Studi Pada Karyawan PT. Donindo Kota Banjarmasin) - Rahmi Widyanti; Deli Anhar; Basuki Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Process to improve the skills of the individual in order to get a better career is call career development. And organizational commitment reflects the extent to which an individual knows and tied to the organization. The purpose this study was to understand the career development, organizational commitment and career development to test the influence of organizational commitment of employees in PT.Donindo Kantor Cabang Banjarmasin.The method used in this research is descriptive and analytical techniques used is quantitative analysis. The sampling technique used was purposive sampling with a population of 67 people and a sample of 40 respondents. Data measured using Likert Scale. And then the data is processed by using SPSS 23The research results showed that the influence of career development on organizational commitment of employees PT. Donindo in Banjarmasin showed a quite well criteria and appropriate.